The Media: Freedom & Power: An Examination of Freedom of Expression in America - Dunklee, Jerry; Harris, Frank (Harris and Dunklee, 2002)
A textbook developed for the course of the same title and taught by the authors at the Department of Journalism, Southern Connecticut State University.
Keywords: History; Freedom of the press; Interpretation and construction; Freedom of expression; United States; United States. Constitution. 1st Amendment; United States; Reporters and reporting; dept.jrn; faculty_collection